2014
DOI: 10.1371/journal.pone.0085094
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza Virus 2009 H1N1 and Adenovirus in a High Risk Population of Young Adults: Epidemiology, Comparison of Clinical Presentations, and Coinfection

Abstract: BackgroundIn 2009, pandemic H1N1 influenza virus (2009 H1N1) emerged worldwide, causing morbidity and mortality that disproportionately affected young adults. Upper respiratory infection (URI), largely due to adenovirus, is an endemic cause of morbidity in military training. Whether clinical presentations differ or excess morbidity results from coinfection is unclear.MethodsThe Center for Advanced Molecular Detection evaluates epidemiology and rapid diagnostics of respiratory pathogens in trainees with URI. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Third, we utilized a multiplex PCR assay to assess the prevalence of other viral respiratory pathogens. The prevalence of viral codetection was rather high, even among adult patients, and several fold higher than those reported among military recruits . If these codetections do in fact represent coinfections, it is possible that previous clinical characterizations of adenovirus‐associated illness may have been confounded by the presence of other respiratory viral pathogens …”
Section: Discussionmentioning
confidence: 88%
“…Third, we utilized a multiplex PCR assay to assess the prevalence of other viral respiratory pathogens. The prevalence of viral codetection was rather high, even among adult patients, and several fold higher than those reported among military recruits . If these codetections do in fact represent coinfections, it is possible that previous clinical characterizations of adenovirus‐associated illness may have been confounded by the presence of other respiratory viral pathogens …”
Section: Discussionmentioning
confidence: 88%
“…Moreover, we are proposing that having flu in the past six months is likely to be a social predictor of having diarrhoea around the same period as a result of poor hand hygiene behaviours, instead of a clinical predictor of flu severity. This is also supported by the fact that the association of diarrhoea as a clinical symptom of flu is less likely to be associated with young adults infected with influenza [49,50], compared with children hospitalised with influenza [51,52]. Furthermore, one study had shown the potential impact of good hand hygiene behaviour advocated during influenza pandemic can help to reduce acute diarrhoea during the same period [53].…”
Section: Discussionmentioning
confidence: 92%
“…Influenza causes annual epidemics which, in the context of an effective vaccine program, are typically limited in this population, but which can have considerable impact when new strains emerge. In summer and fall of 2009, influenza was responsible for 20% of FRI in those who were tested [ 20 , 21 ]. Large outbreaks of pharyngitis caused by S. pyogenes , complicated by acute rheumatic fever, pneumonia, necrotizing skin and soft tissue infections, and other suppurative and immunologic complications, have been reported throughout the past century, prompting widespread use of antimicrobial prophylaxis at training sites [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%